Overcoming poor ovarian response in assisted reproductive technology programs in patients of late reproductive age - K. V. Uryupina; I. I. Kucenko; E. I. Kravczova; K. A. Arzumanyan; M. N. Musavi (Медицинский вестник Юга России, 2024)
Objective: to increase the effectiveness of in vitro fertilization in patients of late reproductive age by optimizing prepregnancy preparation for the IVF program.Materials and methods: The study included 67 patients of late reproductive age with a history of unsuccessful IVF attempts, divided into two groups at the second stage of the study, depending on the volume of prepregnancy preparation: group 1 (33 patients), group 2 (34 patients). The control group (50 patients) were healthy women of reproductive age. Immunohistochemical examination of the endometrium and microbiological examination of the uterine cavity, hormonal status of peripheral blood, study of the concentration of melatonin in peripheral blood and follicular fluid, antioxidant status of follicular fluid, expression of leukemia inhibitory factor (LIF) in the cervical secretion were performed.Results: in patients with age-related dysregulation of the hypothalamic-pituitary-ovarian axis and impaired fertile function, a systemic and local (in follicles) decrease in melatonin levels was revealed. The studied effects of melatonin suggested that its use in patients of late reproductive age with reduced follicular reserve and a "poor" response to ovarian stimulation may increase the effectiveness of in vitro fertilization (IVF).Conclusions: The inclusion in the pre-gravidar preparation of a complex of water-soluble polypeptide fractions of the epiphysis, stimulating the production of endogenous melatonin, made it possible to increase the effectiveness of IVF in patients by an average of 3.1 times according to the criterion of "clinical pregnancy" and 4.1 times according to the criterion of "live birth".